Potentialités du débat éthique en termes d'anticipation adaptative des inégalités scolaires et sociales - Karine Demuth-Labouze
On the basis of experimental results, this article develops the hypothesis that the practice of the ethical debate would contribute to fight against the school and social inequalities by influencing both pupils and teachers. Enabling pupils to acquire capabilities, to increase their power of action and to get success outcomes, this practice improves the self-perceptions of the most vulnerable of them. Disrupting teachers' posture and modifying their judgments on pupils, this practice positively influences the self-image of the most disadvantaged. The practice of ethical debate thus improves the two components of the pupils' self-esteem. By this way, and by offering the opportunity to deepen the relationship to oneself and the world, it would promote school achievement for the vulnerable pupils and would widen their range of possibilities by modifying their relation to the future.